2020
DOI: 10.1039/d0nr05287f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancement in biomedical applications on the surface of two-dimensional materials: from biosensing to tissue engineering

Abstract: This review highlights the importance of the dimensionality and surface interactions of 2D materials with examples of recent biosensing and biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 222 publications
(163 reference statements)
0
28
0
Order By: Relevance
“… 44 , 45 Two-dimensional (2D) nanomaterials such as graphene permit the fabrication of ultrasensitive semiconductors functionalized with bioreceptors for the specific detection of small molecules, proteins, and DNA. 45 48 …”
Section: The Nanodiagnostic Devices Scenariomentioning
confidence: 99%
“… 44 , 45 Two-dimensional (2D) nanomaterials such as graphene permit the fabrication of ultrasensitive semiconductors functionalized with bioreceptors for the specific detection of small molecules, proteins, and DNA. 45 48 …”
Section: The Nanodiagnostic Devices Scenariomentioning
confidence: 99%
“…Two-dimensional (2D) nanomaterials have come into the limelight starting with the discovery of graphene in 2004 [34]. Besides atomic layer thickness, tunable electronic properties, good mechanical strength and chemical activity, they feature a high surface-to-volume ratio making them good candidates for electrochemical biosensing, gas sensing, energy conversion, storage devices and many other biomedical applications [35][36][37][38]. Besides graphene and its derivatives, research has focused on the development of other emerging 2D nanomaterials including boron nitride, graphite carbon nitride, transition metal dichalcogenides, MXenes, black phosphorous, transition metal oxides and also, more recently, heterostructures incorporating at least one 2D nanomaterial [39][40][41].…”
Section: Nanomaterial-based Electrochemical Biosensorsmentioning
confidence: 99%
“…Graphene and GO play an important role in the medical and electronic fields due to their antibacterial properties and detection capabilities ( Yeet al., 2015 ). In the last several decades, two-dimensional materials have been the most widely used materials for the manufacture of biosensors due to their high affinity, cost-effectiveness and ease of use ( Nguyen et al., 2020 ). Studies have shown that GO and graphene have antibacterial and antiviral properties ( Akhavan et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%